The potential of the social employment fund and SmartStart using a lean and scalable model to transform ECD in South Africa - Muller, Danick Jude (Rhodes University, 2026)
Early Childhood Development (ECD) is widely recognised for its high returns. as reflected in progressive legislation from the South African government. However, the provision of ECD services has encountered significant challenges, with gaps widening over time. Given that wealthier families can access private sector services, lack of access to quality ECD services is incident on low-income households exacerbating inequality. Models of lean (i.e. least-cost methods of achieving threshold developmental outcomes) ECD delivery to poor communities have been developed, and their impact demonstrated. The main challenge in South Africa is scale: how, given scarce resources and capacity, to move from examples of lean ECD delivery towards achieving universal access, while still meeting ECD quality thresholds and maintaining adequate governance. The question of scale involves much more than designing lean models then working out cost-per child and multiplying by the number of children. What is needed is an understanding of the system of delivery, from the policymaker, through the meso-level (funders, systems-designers, managers, etc.) down to ECD delivery to the child. Such a system needs to be flexible to different contexts and responsive to local communities. The study focuses on two separate, but convergent initiatives at the meso-level in South Africa. These are the government’s Social Employment Fund (SEF) and SmartStart, a Civil Society Organisation that positions itself as a platform and coordinator in the sector, rather than as a direct provider. The research aims to investigate whether these initiatives represent an emerging mode of delivery with the potential to significantly transform the ECD sector, particularly because of their focus on partnerships and empowering civil society. This mode of delivery could also provide lessons for how the government can better interact with poor communities in other policy spheres. The primary research method is thematic analysis based on semi-structured interviews with members of the management teams of the focal organisations (the SEF, SmartStart, and partner organisations) and well-placed individuals outside the focal organisations.
Keywords: Uncatalogued